The Provocative Roles of Platelets in Liver Disease and Cancer - Kanikarla Marie, Preeti; Fowlkes, Natalie W.; Afshar-Kharghan, Vahid; Martch, Stephanie L.; Sorokin, Alexey; Shen, John Paul; Morris, Van K.; Dasari, Arvind; You, Nancy; Sood, Anil K.; Overman, Michael J.; Kopetz, Scott; et al. (Frontiers in Oncology, 2021)
Platelets and the liver play an important role in the process of coagulation and innate immunity. Platelet responses at the site of an injury are rapid. Their immediate activation and structural changes minimize the loss of blood. The majority of the proteins involved in coagulation are produced by the liver. The liver is a multifunctional organ that also plays a critical role in many processes such as metabolism of fats, proteins, carbohydrates, drug metabolism, and toxin removal. Chronic inflammation, trauma or other causes of irreversible damage to the liver can dysregulate these pathways leading to organ and systemic abnormalities. Cirrhosis of the liver is known to increase the risk of bleeding as well the risk of prothrombotic events in patients with consequent activation of platelets. Activated platelets along with a triggered coagulation cascade not only increases the risk of pro-thrombotic events, but can also contribute to cancer progression and metastasis. Cancer progression and the resulting tissue destruction is comparable physiologically to a persistent, chronic wound. Various cancers, including colorectal cancer, have been associated with increased thrombocytosis, platelet activation, platelet storage granule release and thrombosis that can respond to the use of antiplatelet agents and reduce cancer risk and progression. However, in cancer patients with pre-existing liver disease, who are undergoing chemotherapy, it becomes challenging to manage the risk of thrombotic events due to their inherent bleeding diathesis. Chemotherapy is also known to induce damage to the liver, further increasing the frequency of thrombotic events. Depending on the individual patient risks, all of these factors together can disrupt the fragile balance between pro-coagulant and anti-coagulant processes, heightening thrombogenesis in the liver that could provide a niche for circulating tumor cells to adhere to and promote metastasis as well as cancer cell survival in the liver following treatment (i.e. minimal residual disease in the liver).